Low-carbohydrate diets reduce cardiovascular risk factor levels in patients with metabolic dysfunction-associated steatotic liver disease: a systematic review and meta-analysis of randomized controlled trials - Pi, Shanshan; Zhang, Shuwen; Zhang, Junjie; Guo, Yi; Li, Yue; Deng, Jinyan; Du, Hongbo (Frontiers in Nutrition, 2025)
BackgroundLow-carbohydrate diets (LCDs) are increasingly advocated for the treatment of metabolic dysfunction-associated steatotic liver disease (MASLD); however, their cardiovascular safety profile remains controversial. This analysis aims to evaluate the effects of LCDs on cardiovascular risk factors in MASLD patients.MethodsPubMed, Cochrane Library, Web of Science, and Scopus were searched from inception to March 19, 2025. Two reviewers independently conducted data extraction. Meta-analyses were performed using fixed-effects or random-effects models, as determined by the heterogeneity of the included studies. Outcomes included blood pressure, glycemic markers, lipid profiles, and anthropometric indicators. Subgroup analyses explored carbohydrate thresholds (<26% vs. ≥26%) and intervention durations (<24 weeks vs. ≥24 weeks).ResultsSixteen RCTs comprising 1,056 participants were included. LCDs significantly reduced glycated hemoglobin (HbA1c: SMD, −0.27; 95% CI, −0.47 to −0.07), triglyceride (TG: SMD, −0.20; 95% CI, −0.34 to −0.06), body weight (SMD, −0.19; 95% CI, −0.36 to −0.03), and body mass index (BMI: SMD, −0.28; 95% CI, −0.42 to −0.14). Stricter carbohydrate restriction (<26% energy) further improved systolic/diastolic blood pressure, homeostatic model assessment insulin resistance index (HOMA-IR), HbA1c, TG, body weight, BMI, and waist circumference. Short-term interventions (<24 weeks) lowered HbA1c, TG, and BMI.ConclusionThis systematic review and meta-analysis found that LCDs are associated with improvements in cardiometabolic risk factors among patients with MASLD. Furthermore, short-term implementation of a strict carbohydrate-restricted dietary regimen may yield additional clinical benefits. Future research should prioritize: standardized nutrient assessment, enhanced adherence strategies, and cardiovascular endpoint trials.Systematic review registrationPROSPERO: CRD42024603432; https://www.crd.york.ac.uk/PROSPERO/view/CRD42024603432.